Correction: Salivary Antigen SP32 Is the Immunodominant Target of the Antibody Response to Phlebotomus papatasi Bites in Humans. - Soumaya Marzouki; Maha Abdeladhim; Chaouki Ben Abdessalem; Fabiano Oliveira; Beya Ferjani; Dana Gilmore; Hechmi Louzir; Jesus G Valenzuela; Mélika Ben Ahmed (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pntd.0001911.].